2020
DOI: 10.14786/flr.v8i1.485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of first school years on mathematical skill profiles

Abstract: This study investigated the effect of children's first formal school years on mathematical skill profiles, measured by a variety of arithmetical skills and Spontaneous Focusing On Numerosity (SFON) tasks. By using person-centered approach the aim was to investigate whether the amount of formal schooling is associated with mathematical skills in the same way for all children, or, whether the associations differ according to the children's mathematical skill profiles. Data was analyzed from 652 4-7-year-old chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Both Batchelor et al (2015) and Rathé et al (2018) found correlations close to zero when they took measures of children's SFON tendencies using these two approaches. Consistent with these results, Nanu et al (2020) performed an exploratory factor analysis of various SFON items, finding that picture task items loaded together onto one factor while imitation task items loaded together onto another. These findings are concerning for at least two reasons.…”
Section: The Path From Idea To Interventionmentioning
confidence: 57%
“…Both Batchelor et al (2015) and Rathé et al (2018) found correlations close to zero when they took measures of children's SFON tendencies using these two approaches. Consistent with these results, Nanu et al (2020) performed an exploratory factor analysis of various SFON items, finding that picture task items loaded together onto one factor while imitation task items loaded together onto another. These findings are concerning for at least two reasons.…”
Section: The Path From Idea To Interventionmentioning
confidence: 57%
“…The five factors of vocabulary, arithmetic, memorial number, block diagram and number symbols were significantly higher than before the intervention. The difference between the two is very significant at P < 0.01 [10].…”
Section: Comparison Of Cognitive Function Test Scores Of Obese Children After Aerobic Exercise Interventionmentioning
confidence: 83%
“…There are a variety of tasks designed to measure SFON, and studies show that the type of task can have an influence on measured SFON (Batchelor et al, 2015;Rathé et al, 2016;Nanu et al, 2020). According to Hannula (2005), the following criteria are important when assessing SFON.…”
Section: Measuring Sfonmentioning
confidence: 99%